Accessing Electronic Health Records of the Unconscious Patient - Prachi Gurav; Sanjeev Panandikar (ACHSM, 2022)
Electronic Health Records are a digital version of paper-based records. Studying previous treatment, care and medications is important for making diagnosis for the current situation. The aim of this paper relates to the use of EHR as a means of communication between patient and health care provider with a focus on how EHRs communicates health information for unconscious patient to physicians. As accessing records requires credentials of patient and if the patient is not in a condition to enter his credentials, this leads to the scope of dynamic access control. Dynamic access control is provided by dividing EHRs into different levels. The basis for these levels is physician's specialization and patient's health status. This framework is implemented with the help of a WAMP server using PHP and MySQL.